PERDAGANGAN BEBAS ASEAN-CHINA FREE TRADE AREAL (ACFTA) TERKAIT INDUSTRI DAN IKLIM INVESTASI DI INDONESIA - TRI ATIKA FEBRIANY, SH A.21211057, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
ABSTRACTcountries (Indonesia, Thailand , Malaysia , Singapore , Philippines and Brunei Darussalam) with China , which is called the ASEAN -China Free Trade Agreement (ACFTA). These free trade is in the form of a tax rate reduction for goods on a regular basis up to 0% , the tariff reduction program framework of free trade between ASEAN and China, carried out in stages beginning on January 1, 2004 for EHP This thesis discusses about the implication problem of ASEAN - China Free Trade Area focusing on industry and government efforts to mitigate them. Free trade agreement concluded between Indonesia with some countries and China are summarized in the Agreement on Trade in Goods of the Framework Agreement on Comprehensive Economic Cooperation between the Association of Southeast Asian Nations and the People's Republic of China which is more commonly known as the ASEAN - China Free Trade Area. Indonesia bind themselves and joined by what is called the ASEAN- China Free Trade Agreement (ACFTA) , by ratifying the Framework Agreement on Comprehensive Economic Co-operation Between The Association of South East Asian and The People 's Republic of China (ASEAN - China) on 15 June 2004 through Presidential Decree No. 48 of 2004 . Which Indonesia has had to open up the domestic market to the wider ASEAN countries and China. The opening of this market is the embodiment of a free trade agreement between th